A dynamic simulation of high bar movements with bar strain - Yamasaki, T.; Yamamoto, Y.; Gotoh, K. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The kip movements of two expert gymnasts are simulated using a simple rigid three-link model with taking into account dynamic strain of the bar and the measured time history of joint angles. We show that after some parameter identification this model can reproduce the measured kip movements of the gymnasts and the bar strain to some extent. Moreover, we discuss the identified bar parameters that are not entirely consistent to a range of parameters expected from the standard specification of the Federation of International Gymnastics (FIG).